Evaluating the Efficacy of Early Intervention Programs for Children with Developmental Disorders - Moses Adeleke Adeoye; Jamiu Temitope Sulaimon; Samuel Femi Iliasu; Rebecca Omotolani Fawole (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2025)
This paper explores the critical need for standardised diagnostic methods and comprehensive early intervention programs for children with developmental disorders. Recognising the variability in diagnostic practices and the significant disparities in access to support services, the paper advocates for establishing uniform criteria to enhance early identification and intervention. A review of existing early intervention programs highlights the effectiveness of various approaches, yet also underscores the challenges faced in implementation, including resource limitations, public awareness, and cultural barriers. The paper emphasises the importance of family involvement in the intervention process, noting that empowered families can significantly influence developmental outcomes. In conclusion, establishing standardised diagnostic methods and comprehensive early intervention programs is essential for supporting children with developmental disorders. By fostering collaboration among stakeholders and empowering families, we can create a more equitable framework that enhances developmental outcomes for all children. By addressing these interconnected issues, this paper contributes to the ongoing discourse on improving early intervention services for children with developmental disorders, advocating for a more equitable and practical framework that supports the diverse needs of children and their families.